Sintesis dan Uji Aktivitas Antibakteri Senyawa N-Fenil-3,4-Diklorobenzamida (Synthesis and Antibacterial Activity Assay of N-Phenyl-3,4-Dichlorobenzamide) - Vinastika Gita Yualanda; Indah Purnama Sary; Dian Agung Pangaribowo (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
In this research, the synthesis of N-phenyl-3,4-diklorobenzamida was carried out by reacting 1,3-diphenylthiourea and 3,4-dichlorobenzoil chloride via bimolecular nucleophilic substitution reaction (SN2). The assays for the obtained compound product were purity test (tested by TLC and melting point tester), chemical and physical characterization (shape, color, and solubility), confirmation of the compound and structure (performed by UV-Vis spectrophotometer, FTIR spectrometer, 1H-NMR and 13C-NMR). The result showed that the compound was synthesized successfully with a yield of 42%, then the in vitro test of antibacterial activity against Staphylococcus aureus ATCC 6538 and Pseudomonas aeruginosa ATCC 27853 was conducted by well diffusion method. The compound N-phenyl-3,4-dichlorobenzamida did not have antibacterial activity which showed by the absence of inhibition diameter. Keywords: 1,3-diphenylthiourea, N-phenyl-3,4-dichlorobenzamide, nucleophilic substitution, antibacterial